Bridging heterogeneous and homogeneous catalysis : concepts, strategies, and applications - Li, Can; Liu, Yan (Weinheim, Germany : Wiley-VCH, 2014)
There are two main disciplines in catalysis research -- homogeneous and heterogeneous catalysis. This is due to the fact that the catalyst is either in the same phase (homogeneous catalysis) as the reaction being catalyzed or in a different phase (heterogeneous catalysis). Over the past decade, various approaches have been implemented to combine the advantages of homogeneous catalysis (efficiency, selectivity) with those of heterogeneous catalysis (stability, recovery) by the heterogenization of homogeneous catalysts or by carrying out homogeneous reactions under heterogeneous conditions.
Acid-Base Cooperative Catalysis for Organic Reactions by Designed Solid Surfaces with Organofunctional Groups / Ken Motokura, Toshihide Baba, Yasuhiro Iwasawa -- Catalytic Reactions in or by Room-Temperature Ionic Liquids: Bridging the Gap between Homogeneous and Heterogeneous Catalysis / Youquan Deng, Feng Shi, Qinghua Zhang -- Heterogeneous Catalysis with Organic-Inorganic Hybrid Materials / Sang-Eon Park, Eun-Young Jeong -- Homogeneous Asymmetric Catalysis Using Immobilized Chiral Catalysts / Lei Wu, Ji Liu, Baode Ma, Qing-Hua Fan -- Endeavors to Bridge the Gap between Homo- and Heterogeneous Asymmetric Catalysis with Organometallics / Xingwang Wang, Zheng Wang, Kuiling Ding -- Catalysis in and on Water / Shifang Liu, Jianliang Xiao -- A Green Chemistry Strategy: Fluorous Catalysis / Zhong-Xing Jiang, Xuefei Li, Feng-Ling Qing -- Emulsion Catalysis: Interface between Homogeneous and Heterogeneous Catalysis / Yan Liu, Zongxuan Jiang, Can Li -- Identification of Binding and Reactive Sites in Metal Cluster Catalysts: Homogeneous-Heterogeneous Bridges / Michael M Nigra, Alexander Katz -- Catalysis in Porous-Material-Based Nanoreactors: a Bridge between Homogeneous and Heterogeneous Catalysis / Qihua Yang, Can Li -- Heterogeneous Catalysis by Gold Clusters / Jiahui Huang, Masatake Haruta -- Asymmetric Phase-Transfer Catalysis in Organic Synthesis / Shen Li, Jun-An Ma -- Catalysis in Supercritical Fluids / Zhaofu Zhang, Jun Ma, Buxing Han -- Hydroformylation of Olefins in Aqueous-Organic Biphasic Catalytic Systems / Hua Chen, Xueli Zheng, Xianjun Li -- Recent Progress in Enzyme Catalysis in Reverse Micelles / Xirong Huang, Luyan Xue -- The Molecular Kinetics of the Fischer-Tropsch Reaction / Rutger A van Santen, Minhaj M Ghouri, Albert J Markvoort, Emiel J M Hensen -- Index.
Print version record.
Includes bibliographical references at the end of each chapters and index.
Keywords: Catalysis; Catalysis; Catalysts; Heterogeneous catalysis; SCIENCE -- Chemistry -- Physical & Theoretical; Catalysis; Electronic books